Discovering Student's Preferences of Learning English Speaking Activity during PTM Terbatas at MAN 1 Gresik - Nilna Minhatillah; Mas'adatul Hidayah; Safira Elfa Nur (Edulitics (Education, Literature, and Linguistics) Journal, 2022)
Implementation of PTM Terbatas or limited face-to-face meetings affects English learning activities both online and offline. When it comes to learning, selection activity is crucial since it will connect to the learning outcomes. However, the primary objective of this study is to explore the student’s preferences for learning English Speaking skills during PTM Terbatas. This study applied Qualitative research. A series of questionnaires adapted from Huang Huang and Hu has been distributed to 36 students in 12th grade and an interview guideline for the English teacher of MAN 1 Gresik. The result of this study indicated that asking and answering questions with the teacher and playing online games are the most favorable activities. The conclusion is that students prefer asking and answering questions in offline activities while in online activities, they like playing online games more than other online activities.